2017
DOI: 10.3389/fphys.2017.00947
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Biomarkers Correlated with the TNM Staging and Overall Survival of Patients with Bladder Cancer

Abstract: Objective: To identify candidate biomarkers correlated with clinical prognosis of patients with bladder cancer (BC).Methods: Weighted gene co-expression network analysis was applied to build a co-expression network to identify hub genes correlated with tumor node metastasis (TNM) staging of BC patients. Functional enrichment analysis was conducted to functionally annotate the hub genes. Protein-protein interaction network analysis of hub genes was performed to identify the interactions among the hub genes. Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 66 publications
3
84
0
1
Order By: Relevance
“…24 Several previously publications have uncovered that TOP2A is a poor prognostic biomarker in BCa. [25][26][27] In addition, Zeng et al 28 In conclusion, our study revealed that the prognostic model based on comprehensive study including WGCNA, DEGs screening and LASSO Cox regression has reliable reproducibility and accuracy in predicting prognosis of BCa and even pan-cancer.…”
Section: Discussionmentioning
confidence: 55%
“…24 Several previously publications have uncovered that TOP2A is a poor prognostic biomarker in BCa. [25][26][27] In addition, Zeng et al 28 In conclusion, our study revealed that the prognostic model based on comprehensive study including WGCNA, DEGs screening and LASSO Cox regression has reliable reproducibility and accuracy in predicting prognosis of BCa and even pan-cancer.…”
Section: Discussionmentioning
confidence: 55%
“…Consistently, profiling the age‐related stomach adenocarcinoma in young and old subjects also reveals altered genes in cell cycle and muscle system . Recent studies also show genes involved in apical junction might also play role in cancer development . Collectively, these common oncogenic pathways and uncharacterized pathways might together contribute to the invasive feature of cancer in elder patients.…”
Section: Resultsmentioning
confidence: 72%
“…16 Recent studies also show genes involved in apical junction might also play role in cancer development. 17 Collectively, these common oncogenic pathways and uncharacterized pathways might together contribute to the invasive feature of cancer in elder patients. These pathways might collectively contribute resistance to current cancer therapies and make the elder cancer patients response poorly.…”
Section: Aging Widely Impacts Specific Pathways Across Cancersmentioning
confidence: 99%
“…The remaining three genes turn out to have a positive impact on patients’ survival time. Among the five risk genes, CDCA8 was found to be correlated with bladder cancer and was abundantly expressed in bladder cancer samples . And the high expression of CDCA8 was regarded as an adverse predictor of survival time for patients with bladder cancer.…”
Section: Discussionmentioning
confidence: 98%